Forming the South Asian Diaspora: The Use of Instagram as an Identity and Community Building Platform - Sadat, Marwa (Université d'Ottawa / University of Ottawa, 2025)
As social media becomes increasingly embedded in our lives, this thesis focuses on a specific niche within the expansive and ever-evolving social media landscape. Through digital ethnographic research and semi-structured interviews with participants, the study examines how South Asian diasporic leftist activists in Canada and the United States strive to build community and identity on Instagram. By creating a space on the platform to express what they describe as their authentic selves, these activists, primarily women from regions they identify as either South Asian or SWANA (South West Asian and North African), share their artistic endeavours, whether through photography, curated to achieve aesthetic appeal or captured by themselves, as well as written works and other forms of creative expression. Their work is deeply intertwined with their identities; as women of colour and feminists, they leverage their platforms to address issues that impact them and their communities, fostering a space that elevates marginalized voices through online techniques. In Chapter One, I examine how Instagram has developed and evolved into its current form, focusing on the role of users, other key stakeholders, and competition from other social media platforms in capturing engagement and attention. In Chapter Two, I explore how activists present themselves on this platform, create communities through activism, and challenge stereotypes and Islamophobia. Additionally, I analyze the backlash these activists face and how it serves as a tool to contest narratives surrounding their own identities. Finally, using the ongoing war in Gaza in 2023 as a case study, I investigate how these activists mobilized discussions around this genocide and the challenges they encountered in striving to be seen as virtuous advocates. I will conclude this thesis by discussing the intricacies of conducting research online, including its benefits and the potential negative impacts on users, particularly researchers. -- À mesure que les réseaux sociaux deviennent de plus en plus ancrés dans nos vies, cette thèse se concentre sur une niche spécifique dans le paysage expansif et en constante évolution des médias sociaux. Au moyen d'une recherche ethnographique numérique et d'entretiens semi-structurés avec les participant·e·s, l'étude examine comment les militants de gauche de la diaspora sud-asiatique au Canada et aux États-Unis s'efforcent de construire une communauté et une identité sur Instagram. En créant un espace sur la plateforme pour exprimer ce qu'ils décrivent comme leur « moi authentique », ces militants, principalement des femmes originaires de régions qu'ils identifient comme étant soit sud-asiatiques, soit SWANA (South West Asian and North African), partagent leurs efforts artistiques, que ce soit par le biais de la photographie, conçue pour atteindre un attrait esthétique ou capturée par eux-mêmes, ainsi que des œuvres écrites et d'autres formes d'expression créative. Leur travail est profondément lié à leurs identités ; en tant que femmes racisées et féministes, elles utilisent leurs plateformes pour aborder des enjeux qui les concernent elles-mêmes et leurs communautés, créant un espace qui valorise les voix marginalisées grâce à des pratiques en ligne. Dans le premier chapitre, j'examine comment Instagram s'est développé et transformé jusqu'à sa forme actuelle, en me concentrant sur le rôle des utilisateur·rice·s, d'autres acteurs clés, ainsi que sur la concurrence d'autres plateformes sociales dans la captation de l'engagement et de l'attention. Dans le deuxième chapitre, j'explore comment les activistes se présentent sur cette plateforme, créent des communautés d'activisme, et remettent en question les stéréotypes et l'islamophobie. J'analyse également les réactions négatives auxquelles ces activistes sont confrontées, et comment ces retours deviennent des outils leur permettant de contester les récits entourant leurs propres identités. Enfin, en utilisant la guerre en cours à Gaza en 2023 comme étude de cas, j'examine comment ces activistes ont mobilisé des discussions autour de ce génocide et les défis auxquels elles ont été confrontées dans leur quête pour être perçues comme des défenseures légitimes. Je conclurai cette thèse en discutant des subtilités de la recherche en ligne, y compris ses avantages et les impacts potentiellement négatifs sur les utilisateur·rice·s, en particulier les chercheur·e·s.
Keywords: South Asian Diaspora; Instagram communities; Social Media Activism; Online Hate, backlash and misogyny; SWANA (South West Asian and North Africa) Diaspora; Digital Ethnography; Diasporic leftist activism; Digital Self-Representation; Virtuous advocacy